Brain metastases in patients with low-grade endometrial carcinoma - Paulina Cybulska; Marina Stasenko; Raanan Alter; Vicky Makker; Karen A. Cadoo; Yukio Sonoda; Nadeem R. Abu-Rustum; Jennifer J. Mueller; Mario M. Leitao, Jr (Elsevier, 2018)
Objective: To report characteristics of patients with low-grade endometrioid endometrial carcinoma (EC) who develop brain metastases. Methods: We retrospectively identified all patients treated at our institution for FIGO grades 1/2 EC from 1/2000-12/2016, who developed brain metastases. Electronic medical records were reviewed, data abstracted. Overall survival (OS) was determined from time of brain metastases to death or last follow-up. Appropriate statistical tests were used. Results: Of 3052 patients, 23 (9, grade 1; 14, grade 2) developed brain metastases (incidence = 0.75%). Presentation at initial diagnosis: median age = 61.3 years (range, 41-81); median BMI = 29.8 kg/m2 (range, 20.3-42.6 kg/m2); distribution by stage: I, 15/23 (65%); II, 2/23 (8.7%); III, 3/23 (13.0%); IV, 3 (13.0%). None showed clinical evidence of brain metastases at presentation. Median time to diagnosis of brain metastases = 29.7 months (range, 6-145); median age = 64.6 years (range, 47.5-86.5). Brain metastases were the first, isolated site of recurrence in 2/23 (9%). All presented with neurological symptoms. Six (26%) had solitary brain lesions. Seventeen (74%) received treatment; 6 (28%), supportive care only. Median OS for patients receiving any treatment = 5.8 months (95% CI, 1.6-10.0), versus 2.4 months (95% CI, 1.5-3.3; p = .04) for best supportive care. Conclusion: Brain metastases in low-grade EC is rare, prognosis generally poor. Compared to supportive care only, any treatment results in more favorable outcomes. Keywords: Brain metastases, Endometrial carcinoma, Low-grade endometrial carcinoma